2020
DOI: 10.1101/2020.07.13.20152397
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Women in power: Female leadership and public health outcomes during the COVID-19 pandemic

Abstract: Some countries have been more successful than others at dealing with the COVID-19 pandemic. When we explore the different policy approaches adopted as well as the underlying socio-economic factors, we note an interesting set of correlations: countries led by women leaders have fared significantly better than those led by men on a wide range of dimensions concerning the global health crisis. In this paper, we analyze available data for 35 countries, focusing on the following variables: number of deaths per capi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 11 publications
2
43
1
1
Order By: Relevance
“…From an economic point of view, understanding the causal impact of women’s leadership on outcomes is a difficult task, yet necessary to draw policy conclusions ( Profeta 2020) . To this respect, the study by Coscieme et al. (2020) is not conclusive.…”
Section: Female Leadership and Policymentioning
confidence: 87%
See 1 more Smart Citation
“…From an economic point of view, understanding the causal impact of women’s leadership on outcomes is a difficult task, yet necessary to draw policy conclusions ( Profeta 2020) . To this respect, the study by Coscieme et al. (2020) is not conclusive.…”
Section: Female Leadership and Policymentioning
confidence: 87%
“…A recent study by Coscieme et al. (2020) analyzes 35 countries and shows that countries led by female leaders experienced fewer COVID-19 deaths per capita and were more effective and rapid at flattening the epidemic’s curve, with lower peaks in daily deaths.…”
Section: Female Leadership and Policymentioning
confidence: 99%
“…More generally, countries with female leaders have done better at securing public confidence and adherence to new measures than have countries with male leaders. 17 In England, controversy surrounding a trip made during lockdown by a close adviser to the prime minister has substantially undermined public confidence in the government and support for the measures that it was taking. 18 In Hong Kong, continuing political unrest has substantially eroded public trust in the government, although the community has generally shown a high level of adherence that could be attributable to lessons learnt from the previous outbreak of SARS in 2003.…”
Section: Community Engagementmentioning
confidence: 99%
“…A recent study indicated that countries with women in positions of leadership suffered six times fewer deaths from COVID-19 as countries with governments led by men. 14 Recognising the effectiveness of countries led by women may help in understanding the underlying prerequisites of effective leadership. Societies who elect female leaders may share a different set of values and perspectives, including gender equality, than more traditional societies.…”
Section: Effective Change Calls For Bold Solutionsmentioning
confidence: 99%